Increased Expression of Mitochondrial UQCRC1 in Pancreatic Cancer Impairs Antitumor Immunity of Natural Killer Cells via Elevating Extracellular ATP - Cong, Hui; Gao, Jian; Wang, Qing; Du, Min; Li, Huimin; Li, Qian; Li, Jin; Liang, Yiyi; Zhao, Dan; Yang, Hancao; Gan, Yu; Tu, Hong (Frontiers in Oncology, 2022)
Pancreatic cancer (PC) is one of the most lethal malignancies characterized by a highly immunosuppressive tumor microenvironment (TME). Previously, we have reported that ubiquinol-cytochrome c reductase core protein I (UQCRC1), a key component of mitochondrial complex III, is generally upregulated in PC and produces extracellular ATP (eATP) to promote PC progression. Here, we sought to investigate whether the oncogenic property of UQCRC1 is generated through its effects on natural killer (NK) cells in the TME. We found that UQCRC1 overexpression in PC cells inhibited cytotoxicity of NK cells, as well as the infiltration of NK cells toward PC, whereas knockdown of UQCRC1 enhanced the cytotoxicity and chemotaxis of NK cells. Adoptive NK cell therapy in the subcutaneous mouse model and CIBERSORTx analysis with human PC specimens confirmed UQCRC1 elicited immunosuppressive effects on NK cells. Such UQCRC1-induced impairment of NK cells was mediated by eATP and its metabolite adenosine via P2Y11R and A2AR, respectively. Mechanistically, we found the UQCRC1/eATP axis reduced the expression of chemokine CCL5 in cancer cells and altered the balance of activating receptor DNAM-1 and inhibitory receptor CD96 on NK-92MI cells, resulting in decreased chemotaxis and exhausted phenotype of NK-92MI cells. Taken together, our study provides the evidence to support a novel mechanism by which energy metabolism change in cancer cells remodels the TME and impedes NK cell surveillance. It also suggests that targeting UQCRC1 may be a potential combined strategy for PC immunotherapy.